2017
DOI: 10.1016/j.biopha.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of quercetin in collagen-induced arthritis

Abstract: Quercetin, a bioactive flavonoid with anti-inflammatory, immunosuppressive, and protective properties, is a potential agent for the treatment of rheumatoid arthritis (RA). Collagen-induced arthritis (CIA) is the most commonly used animal model for studying the pathogenesis of RA. This study analysed the therapeutic role of quercetin in collagen-induced arthritis in C57BL/6 mice. The animals were allocated into five groups that were subjected to the following treatments: negative (untreated) control, positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 44 publications
3
79
1
2
Order By: Relevance
“…[58] The multifaceted therapeutic applications of quercetin on ageing, allergy, angiogenic properties, cancer, inflammation, obesity, arthritis, asthma, diabetes exercise performance, gastroprotection, prostate adenocarcinoma, immunity and infections were extensively reviewed. [59] Therapeutic treatment of CIA with quercetin decreases the severity of arthritic inflammation, protects joints from cartilage and bone damage, [60] and ameliorated all markers of inflammation and oxidative stress measured. [61] It has also been reported that quercetin reduces the production of cytokines, including TNF-a, INF-c and IL-6, [60] which was also observed in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] The multifaceted therapeutic applications of quercetin on ageing, allergy, angiogenic properties, cancer, inflammation, obesity, arthritis, asthma, diabetes exercise performance, gastroprotection, prostate adenocarcinoma, immunity and infections were extensively reviewed. [59] Therapeutic treatment of CIA with quercetin decreases the severity of arthritic inflammation, protects joints from cartilage and bone damage, [60] and ameliorated all markers of inflammation and oxidative stress measured. [61] It has also been reported that quercetin reduces the production of cytokines, including TNF-a, INF-c and IL-6, [60] which was also observed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…[59] Therapeutic treatment of CIA with quercetin decreases the severity of arthritic inflammation, protects joints from cartilage and bone damage, [60] and ameliorated all markers of inflammation and oxidative stress measured. [61] It has also been reported that quercetin reduces the production of cytokines, including TNF-a, INF-c and IL-6, [60] which was also observed in this work. Kaempferol, a flavonol also described in the C. ambrosioides extract, showed an antiosteoclastogenic effect [62] and attenuated the severity of arthritis in mice with CIA, which might be associated with its inhibitory effect on the activation of the MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has proven to maintain rheumatoid arthritis in a rat model. 2,13 In this research, we challenged the QUE to treat a severe lupus nephritis mice model and then we measured the biomarkers of T cell dependent pathway of lupus pathogenesis. At the first biomarker, we found an inspiring result in the T reg marker of CD4 + CD25…”
Section: Discussionmentioning
confidence: 99%
“…Pri podganah so ugotovili, da ima varovalni učinek na kardio-vaskularni sistem (Rendig et al 2001) in da deluje protivnetno (Gardi et al 2015). Kvercetin se je izkazal tudi kot učinkovito sredstvo za zdravljenje revmatoidnega artritisa pri miših (Haleagrahara et al 2017) in je bil učinkovit pri preprečevanju poškodb očesne mrežnice zajcev, ki nastajajo kot posledica svetlobe (Wang et al 2017). Za kvercetin je bilo ugotovljeno, da vzpodbuja delovanje imunskega sistema pri miših (Singh et al 2017).…”
Section: Kvercetinunclassified